Georgia : Poverty assessment - World Bank (World Bank, 2012)
This report presents a comprehensive analysis of poverty and its main determinants using the most recent 2007 Living Standards Measurement Survey (LSMS) data. It provides an in-depth analysis of rural poverty, the linkages between labor markets and poverty, the importance of social transfers for poverty alleviation, and the progress made since 2003 in the health and education sectors, and also presents some findings on incomes trends based on the Household Budget Survey from 2003 to 2006. The report also simulates possible poverty impacts from the dual shocks of the August 2008 conflict and the current global financial crisis. Main messages in the document are: (1) the available data indicate that living standards in Georgia have improved in many dimensions since 2003; (2) poverty in Georgia continues to be deeply entrenched in rural areas, accounting for 60 percent of the poor; (3) the performance of the labor markets has so far not contributed much to poverty reduction; (4) social assistance became an increasingly important lifeline for Georgia's poor; (5) the double shocks of the August 2008 conflict and the global financial crisis risk undermining the poverty reduction effort; and (6) the poverty reduction strategy of the government of Georgia should focus on: extending the coverage of the Targeted Social Assistance to reach more of the poor; promoting investments in infrastructure and creating opportunities for off-farm employment in rural areas; and continuing reforms in the health and education sectors to improve human capital, which is the prerequisite for sustainable economic growth and poverty reduction. The main findings state that since 2003, Georgia has implemented an impressive array of reforms. Unfortunately, the absence of comparable household surveys over time precludes a proper analysis of the impact of these reforms on growth and poverty reduction.